Imported Plasmodium vivax malaria with severe thrombocytopaenia: can it be severe malaria or not?. (December 2016) - Antinori, Spinello; Corona, Alberto; Ridolfo, Anna; Galimberti, Laura; Ricaboni, Davide; Milazzo, Laura; Corbellino, Mario
Abstract Background Thrombocytopaenia is the most frequent malaria-associated haematologic alteration observed with all fivePlasmodium parasites causing disease in humans. Although not included in the World Health Organization criteria for severePlasmodium falciparum malaria, severe thrombocytopaenia has been increasingly mentioned as an indicator ofP. vivax malaria severity. Case Here, it is described a case of importedP. vivax malaria in a 37-year old man from Pakistan who presented with severe thrombocytopaenia (5 × 109 /L). He was admitted to the intensive care unit and initially treated with a 1-day course of intravenous quinine followed by oral chloroquine and primaquine. The patient's platelet count increased as early as 4 hours after treatment inception and the clinical course was favourable and uneventful. Discussion This case report, along with a review of published cases focusing on the relationship between thrombocytopaenia and severeP. vivax malaria, suggests that the prognostic role of severe thrombocytopaenia is ambiguous in absence of severe haemorraghic complications and its use as diagnostic criterion of malaria severity may lead to overestimation of severeP. vivax malaria cases. Conclusion Due to the lack of high quality studies it is at present unclear if severe thrombocytopaenia in the setting ofP. vivax malaria should be considered indicative of severe malaria.